Research progress and hotspot analysis of type B aortic dissection: a bibliometric analysis from 2004 to 2023 - Zhen-Yi Zhao; Shu-Li Zhou; Yun Peng; Can Cui; Liang-Geng Gong (Journal of Cardiothoracic Surgery)
Abstract This study aimed to analyze and visualize the research on type B aortic dissection (TBAD) over the past 20 years through bibliometric research. To reveal the development process of TBAD research and the transitions of research hotspots. Literatures was retrieved from the Web of Science Core Collection. The analysis utilized tools such as Microsoft Office Excel, VOSviewer and CiteSpace for bibliometric mapping and visualization, including assessing publication volumes and constructing collaborative networks and keyword burst graphs. A total of 1391 related articles or reviews on TBAD were included. The number of annual publications is steadily increasing. China was the top country in terms of the number of publications. University of Michigan (n = 60) was the most productive university. The Journal of Vascular Surgery (n = 183) was the most published and co-cited journal. Keywords burst analysis showed that “guidelines”, “spinal-cord ischemia”, “society”, “impact”, and “aortic remodeling” were the most frequently used keywords in recent years. In general, the research focus of TBAD has gradually changed from selecting the surgical method to the best clinical management and patient prognosis after thoracic endovascular aortic repair (TEVAR). Promoting positive aortic remodeling and aortic hemodynamics may be the research hotspots in the future.